Environmental aspects of the corporate social responsibility = Środowiskowe aspekty w społecznej odpowiedzialności przedsiębiorstwa - Misztal, Agnieszka; Jasiulewicz-Kaczmarek, Małgorzata (Zielona Góra: Faculty of Economics and Management Press)
The article is dealing with the environmental corporate responsibility. Taking this research topic stems from a growing awareness of entrepreneurs in this area and is associated with the popularity of proving the social responsibility before a group of stakeholders.
Keywords: społeczna odpowiedzialność przedsiębiorstw (SOP); system zarządzania środowiskowego; CSR; corporate social responsibility; environmental management system